Wang Gongbi’s Reception and Localization of New Villageism - Yu, Yan (Education Insights, 2026)
This paper critically examines the historical reception of "New Villageism" by modern Chinese intellectuals, focusing specifically on its constructive localization through the pioneering practice of Wang Gongbi in Henan Province during the Republican era. Driven by the urgent pursuit of national revitalization and comprehensive rural development, Wang initiated the ambitious "Youth Village" project in Xiaowuying, Xihua County. Grounded deeply in local socio-economic realities, he systematically implemented a constructive localization strategy across three major interconnected dimensions. Politically, the initiative focused on improving grassroots self-governance structures and ensuring community security amidst regional instability. Economically, the project aimed at alleviating the severe financial burdens placed on peasants while simultaneously promoting advanced agricultural production techniques to ensure sustainable livelihoods. Furthermore, in the cultural-educational sphere, Wang dedicated significant efforts to popularizing foundational education and advocating for progressive social customs to eradicate outdated traditions. Although this comprehensive rural experiment was eventually suspended due to the overwhelming macro-historical conflicts and severe social constraints of the era, Wang’s enduring endeavors demonstrated the profound dedication and practical wisdom of modern intellectuals seeking structural social reform and educational modernization. Ultimately, this historical analysis offers valuable insights and enduring lessons for contemporary policymakers and scholars exploring sustainable rural development, community empowerment, and effective governance pathways that are authentically suited to specific national conditions and local contexts.